If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3ax + -1x = 0 Solving 3ax + -1x = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add 'x' to each side of the equation. 3ax + -1x + x = 0 + x Combine like terms: -1x + x = 0 3ax + 0 = 0 + x 3ax = 0 + x Remove the zero: 3ax = x Divide each side by '3x'. a = 0.3333333333 Simplifying a = 0.3333333333
| 2/3x+5/5x | | 3x+5=-10+x | | 10.35(3)(15)=a | | x^2+2/3x-26/9 | | 6/8x=72 | | 33(x+2/5)=x-1/3 | | 10.35(3)(15)=465.75 | | x^2+y^2+10x+12y+61=0 | | -4x+6=3x+-8 | | 1000/9.81 | | 52-3x=24x+16 | | 1+x^4-2x^2+1.96x^2=1.0096x^4 | | -6x+7=10-5x | | 60+.6x=.8x | | (w+8)(w-3)=0 | | 60+.6=.2 | | 5x+10=64-4x | | 5y^2+9=3y | | y^2=6y+7 | | 6x+13=35-3x | | (3d+2)(7-1)=0 | | -4x-10=46+5x | | (1/3x)=9 | | 4x+1=60 | | 5x-16=4x+5 | | x-10=-21+2x | | x^2=5+4x | | x+7=-0 | | 5+7=3x | | x^2=y^4-77 | | y=5-8x | | 12x-10=4x-5 |